Severe colic in a newborn dairy calf caused by a large colostrum curd: a case report - Sockett, Donald C.; Pohly, Andrea E.; Deering, Kathleen M.; Breuer, Ryan M. (Frontiers in Veterinary Science, 2024)
A newborn female, Holstein calf weighing approximately 38.5 kg developed severe, persistent colic caused by a large colostrum curd located within the calf’s abomasum. Based upon 10% body weight, the calf had been fed 4 liters (L) of first-milking colostrum approximately 30 min after birth and an additional 2 L of first-milking colostrum 6 h after the first feeding. Both the first and second feedings used an esophageal tube feeder to deliver the colostrum. Colic developed shortly after the second colostrum feeding. The affected calf did not respond to on-farm supportive medical therapy and was humanely euthanized by a penetrating captive bolt approximately 22 h after the onset of colic. This on-farm colostrum feeding protocol is routinely observed in the current dairy industry. This case demonstrates calves that are fed large volumes of colostrum during a relatively short window of time may develop a large, firm colostrum curd within the abomasum that causes abdominal distension, colic, and occasional death. There is an urgent need for prospective analytical studies that determine the optimal immunoglobulin mass (g/L) and the ideal volume of colostrum fed to newborn calves for both the first and second colostrum feedings within the most beneficial time frame. Guidelines should be developed that minimize complications that adversely affect calf health and well-being while ensuring the successful transfer of passive immunity.